Androgenic hormones in crustacean aquaculture: a review - Harlioglu, Muzaffer Mustafa; Farhadi, Ardavan (Tubitak Scientific & Technological Research Council Turkey, 2022)
Increased demands of the seafood market have led to the rapid growth in crustacean aquaculture production in various parts of the world. Therefore, an expansion in the knowledge of the reproductive biology of crustaceans has become more important. Hormones released from the androgenic gland (AG) in crustaceans are liable for both the separation of primary and secondary sexual features and reproductive behavior. AG removal in male crustaceans causes a transformation of the intersex animals towards the females and a degeneration of spermatids and reproductive organs. AG implantation and injection of AG extracts are common approaches for crustacean masculinization. In this review, the importance of AG and its implication in crustacean aquaculture are reiterated, while the discovery, identification, chemical nature, and isolation of insulin-like androgenic gland hormone are also overviewed.
Keywords: Decapod; reproduction; gland implantation; feminization; masculinization; shrimp; crab; crayfish